UNSUR MELAWAN HUKUM DALAM PASAL 362 KUHP TENTANG TINDAK PIDANA PENCURIAN - Jatiana Manik Wedanti, I Gusti Ayu; Sukranatha, A. A. Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013)
Against the law in the formulation of a crime of theft under Article 362 of the CriminalCode gives the sense that every act of taking the property of others can be termed as anact against the law if the act of taking the property of others based on the will or evilintent to have the goods. To declare that the act was against the law, must be provedfirst that the person taking the property of others and not his, have an awareness of hisactions were unlawful and malicious intent to have the item before the imposition of acriminal penalty. Writing method using normative juridical approach and the resultspresented in a descriptive study to describe and analyze the problem.
Keywords: Against the law, Criminal law, Crime, Theft